Fund Collection Products with Mudarabah Agreements in Sharia Financial Institutions: Produk Penghimpun Dana dengan Akad Mudarabah di dalam Lembaga Keuangan Syari’ah - Erniwati (Syamilah Publishing, 2024)
The mudarabah agreement is one of the important financial instruments in sharia financial institutions, which functions as an alternative to the conventional usury-based banking system. This contract involves collaboration between capital providers and business managers, where profits are shared according to the agreement. This research uses a qualitative approach by analyzing various sources, including scientific journals and related literature. Data was collected through a literature study that explores the arguments of the Al-Qur'an, hadith, and relevant rules of mu'amalah fiqh. The aim of this research is to understand in depth the definition, conditions and pillars of mudarabah contracts, as well as how they are implemented in institutions. Islamic finance. This research also aims to compare the practice of mudarabah contracts in sharia financial institutions with similar transactions outside these institutions. The results of the research show that mudarabah contracts have clear terms and conditions, including capital which must be in the form of money and an agreement regarding profit sharing. The implementation of this agreement in financial products such as savings, deposits and working capital financing in sharia banks has proven effective in improving community welfare. Mudarabah contracts not only provide an alternative for people who avoid usury, but also contribute to sharia-based economic growth.